Incidence of and risk factors for acute respiratory distress syndrome in patients admitted to surgical intensive care units: The multicenter thai university-based surgical intensive care unit (THAI-SICU) study - Onuma Chaiwat (2018)
© 2016, Medical Association of Thailand. All rights reserved. Objective: The incidence and outcomes of acute lung injury (ALI)/acute respiratory distress syndrome (ARDS) are unclear. We evaluated the cumulative incidence of, risk factors for, and outcomes of ALI/ARDS in surgical ICUs (SICUs). Material and Method: The multicenter Thai University-based Surgical Intensive Care Unit (THAI-SICU) study was a prospective, observational cohort study including nine university-based SICUs throughout Thailand from April 2011 to January 2013. All >18-year-old surgical patients who were admitted to general SICUs were recruited. The primary outcome was the incidence of ALI/ARDS. Results: In total, 4,652 patients were analyzed. ALI/ARDS new developed in 114 patients (2.5%). Patients with ALI/ARDS had higher APACHE II (20.0 vs. 11.4, respectively; p<0.001) and SOFA scores (7.3 vs. 3.1, respectively; p<0.001) and a higher incidence of past or current smoking (48% vs. 36%, respectively; p<0.001) than the non-ARDS patients. The 28-day mortality rate was significantly higher in patients with than without ALI/ARDS (50% vs. 12%; p<0.001). Higher APACHE II and SOFA scores and higher rates of current or past smoking were independent predictors of ALI/ARDS. Conclusion: The incidence of ALI/ARDS in the THAI-SICU study was low, but the mortality rate was high. Higher severity scores and smoking were associated with ALI/ARDS.